Desiccated Coconut Residue Based Activated Carbon as an Electrode Material for Electric Double Layer Capacitor - Mohd Adib Yahya; C. W. Z. C. W. Ngah; M. A. Hashim; Musa Ahmad; Mohd Ambar Yarmo (Canadian Center of Science and Education, 2024)
Volume: 7, No: 2